Real-world evidence of cabozantinib in patients with metastatic renal cell carcinoma: Results from the CABOREAL Early Access Program. (January 2021) - Albiges, Laurence; Fléchon, Aude; Chevreau, Christine; Topart, Delphine; Gravis, Gwenaëlle; Oudard, Stéphane; Tourani, Jean M.; Geoffrois, Lionnel; Meriaux, Emeline; Thiery-Vuillemin, Antoine; Barthélémy, Philippe; Ladoire, Sylvain; et al.
Abstract: Background: Real-world data on cabozantinib in metastatic renal cell carcinoma (mRCC) is limited. This study (CABOREAL) reports treatment patterns and outcomes for patients treated with cabozantinib through the French Early Access Program. Patients and methods: This multicentre (n = 26), observational, retrospective study enrolled patients with mRCC who had received ≥1 dose of cabozantinib. Overall survival (OS) was estimated using the Kaplan–Meier method; subgroups were compared using the log-rank test. A multiple Cox regression model assessed predictive factors of OS after cabozantinib initiation. Results: Four hundred and ten recruited patients started treatment between September 2016 and February 2018: the Eastern Cooperative Oncology Group Performance Status ≥2, 39.3%; poor International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) risk, 31.7%; 0–1, 2 and ≥3 previous treatment lines, 25.3%, 33.4% and 41.2%, respectively; bone metastases, 55.9%; brain metastases, 16.8%. Median (min–max) follow-up was 14.4 (0–30) months. Overall, 57.0% of patients had a dose reduction, 15.6% an alternative dose schedule. The median average daily dose was 40.0 mg. Median (quartile [Q]1–Q3) treatment duration was 7.6 (0.1–29.1) months, median OS was 14.4 months, and the 12-month OS rate was 56.5% (95% confidence interval: 51.5–61.2). Most patients (54.4%) received subsequent treatment. Predictive factors associated with longer OS were body mass index ≥25 kg/m 2 (p = 0.0021), prior nephrectomy (p = 0.0109), favourable or intermediate IMDC risk (p < 0.0001) and cabozantinib initiation at 60 mg/day (p = 0.0486). Conclusions: In the largest real-world study to date, cabozantinib was effective in unselected, heavily pretreated patients with mRCC. Initiation at 60 mg/day was associated with improved outcomes. ClinicalTrials.gov identifier: NCT03744585 . Highlights: CABOREAL is the largest real-world study of cabozantinib in metastatic renal cell carcinoma to date. Cabozantinib was effective in these unselected, heavily pretreated patients. Patients received cabozantinib for a median duration of 7.6 months. Dose modifications were necessary in 59% of patients, mainly to manage adverse events. Initiation of cabozantinib at 60 mg/day was associated with improved outcomes.